Trade Promotion Strategies Best Practices - Borgeon, Michel (Business Expert Press, 2012)
Ebook from IG Library ; New opportunities are emerging constantly, as part of the globalization process creating new markets, with new players and challenging current business practices. Creating or exploiting opportunities on an individual basis is not the best practice: it is much more productive (and much less risky) to participate in national Trade Promotion Programs designed and implemented with government assistance. This book will give readers insight into the national strategies, how are they designed and implemented. Special attention is given to evaluation tools created to assess results and provide justification for investment expenditures. Best practices will be considered and reviewed on the basis of selected countries having introduced innovative national trade promotion programs, such as Finland, Mauritius, Mexico, New Zealand and Singapore. In recent years, Trade Promotion Institutions have developed new tools to support the business sector, helping enterprises to find new markets and trade opportunities. This book is here to engage the readers to learn more about these institutions.